Study on preparation of large-grain UO2-SiC fuel pellets and high-temperature oxidation resistance - YAN Chao; YU Xiaohe; HUANG He; HOU Keke; CAO Changqing; LIN Jun; ZHU Zhiyong (He jishu, 2022)
BackgroundThe Uranium dioxide (UO2) is currently the most widely used nuclear fuel for commercial nuclear reactors. However, the Fukushima Daiichi nuclear disaster revealed the primary safety risks of this fuel in an accident, so various international programs were launched to develop accident tolerant fuel (ATF), a new generation of fuel system developed to enhance the capability of nuclear fuel assemblies in severe accidents.PurposeThis study aims to improve the thermal conductivity of fuel pellets by adding a second material to the UO2 matrix, an important research direction for ATF.MethodsFirst of all, large-grain UO2 particles were used as raw materials, and the high-density large grain UO2-SiC composite fuel pellets were obtained by Spark Plasma Sintering (SPS) sintering process at lower sintering temperature. Then, the properties, such as microstructure and chemical composition, of the composite fuel pellets were characterized by using metallographic microscope (MM), scanning electron microscope (SEM), X-ray diffraction (XRD) and energy dispersive spectrometer (EDS). Finally, the high-temperature oxidation resistance in air environment was studied.ResultsThe results show that the UO2-SiC interfacial reaction can be avoided by the SPS sintering at lower temperature, and the density of the prepared pellets is more than 95% theoretical density (TD). Compared with traditional UO2 fuel pellets and SPS sintered UO2-SiC pellets using conventional UO2 powders, the thermal conductivity of large-grain composite fuel pellets is significantly improved. Oxidation tests results indicate that the oxidation weight gain of the composite fuel pellets is significantly weaker than that of traditional pellets when the temperature is lower than 350 ℃. However, when the temperature reaches 350 ℃, the oxidation of UO2 cannot be further prevented by SiC.ConclusionsThis study provides reference for improving the thermal conductivity of UO2 matrix by adding a second phase with high thermal conductivity.